The Role of Technology Usage in Mediating Intellectual Capital on SMEs Performance During the Covid-19 Era - Faisol Faisol; Puji Astuti; Sigit Puji Winarko (ETIKONOMI, 2021)
This study examines technology in mediating human capital, customer capital, and organizational capital on SMEs' performance during Covid-19. To test the hypothesis, the PLS-SEM method was applied. Data collection was conducted by sharing questionnaiers to 150 owners of small industrial cluster in East Java, Indonesia.The empirical results show that human capital and technology usage directly affect significantly on SMEs' performance. Furthermore, technology usage has a significant influence in mediating human capital on firms' performance. We provide implications for using technology for practice and using a socio-technical approach by SMEs to face challenges related to their work organization in response to COVID-19 while maintaining their activities. We hope that our reflection will be a source of thought for scholars and practitioners to explore further using technology for SMEs to secure business continuity during COVID-19.JEL Classification: O2, O34, M21How to Cite:Faisol, Astuti, P., Winarko, S. P. (2021). The Role of Technology Usage in Mediating Intellectual Capital on SMEs Performance During the Covid-19 Era. Etikonomi, 20(2), xx – xx. https://doi.org/10.15408/etk.v20i2.20172.